2023
DOI: 10.1108/ijm-12-2022-0652
|View full text |Cite
|
Sign up to set email alerts
|

The salience of remote leadership: implications for follower self-control and work-life balance

Abstract: PurposeThe purpose of this study was to examine whether remote work moderates the mediated relationship between leadership behavior (transformational leadership and leader incivility), followers' self-control, and work-life balance.Design/methodology/approachThe authors conducted a three-wave, time lagged study of 338 followers. Drawing on social information processing theory, a moderated mediation model was proposed: it was hypothesized that remote work strengthens the relationship between leadership behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The existing literature on remote work arrangements and their impact on work–life balance suggests that remote working can increase the flexibility of work operations and promote work–life balance [ 21 ]. However, this is only possible when organizations provide adequate support to their employees, encourage them to feel a sense of control, and implement work–life balance strategies [ 22 , 23 ]. Studies have also shown that the joint effect of spousal support at home and coworkers’ support at work greatly contributes to perceived work–life balance [ 4 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature on remote work arrangements and their impact on work–life balance suggests that remote working can increase the flexibility of work operations and promote work–life balance [ 21 ]. However, this is only possible when organizations provide adequate support to their employees, encourage them to feel a sense of control, and implement work–life balance strategies [ 22 , 23 ]. Studies have also shown that the joint effect of spousal support at home and coworkers’ support at work greatly contributes to perceived work–life balance [ 4 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence suggests that individuals with high self-control are better able to manage their thoughts and emotions, effectively inhibit negative behaviors, and exhibit higher job achievement than those with low self-control ( de Ridder et al, 2012 ; Converse et al, 2018 ). Self-control is particularly important in remote work, where employees are far from the control and supervision of managers ( Howe and Menges, 2022 ; Walsh et al, 2023 ). Most existing studies examined the influence of organizational and team factors, such as organizational support ( Makikangas et al, 2022 ), human resource practices ( Li et al, 2023 ), and internal communication ( Dhanesh and Picherit-Duthler, 2021 ), while ignoring the importance of employees’ factors in remote work.…”
Section: Introductionmentioning
confidence: 99%